Chemical compositions of tapa leaves (pycnarrhena cauliflora): a natural food flavor enhancer - Nor Azman, Muhammad Farhan Syakir; Mohamad Nazri, Nur Izzah; Suleiman, Monica; Yeaw, Ng Shean; Yusoff, Juliana; Salim, Fatimah (2025)
The leaves of ‘Pokok Tapa’ or scientifically known as Pycnarrhena cauliflora (Menispermaceae) are used by Borneo communities as folkloric medicine and as a natural food flavour enhancer in their cooking. However, a thorough literature search revealed that not much scientific work has been done on the species. Thus, the aim of this study is to determine the chemical compositions of the plant’s leaves through proximate analysis, phytochemical screening, and high-performance liquid chromatography (HPLC) profiling. The proximate analysis indicated that the dried leaves contain key nutritional components such as carbohydrate, crude fibre, total fat, and crude protein in the percentage of 78.5, 59.0, 2.7 and 8.2, respectively. The high protein content could contribute to the flavor enhancer potential of the leaves. Meanwhile, the phytochemical screening test on the methanolic leaf extract showed the presence of several classes of compounds which were alkaloids, terpenoids, and tannins. Among the classes of compounds that have been reported in the Pycnarrhena species were the alkaloids isoquinoline, bisbenzylisoquinoline and aporphine while none of the terpenoids or tannins. The HPLC profile obtained at 230 and 281 nm UV wavelengths indicate strong π→π* and n→π* electronic transitions of the moderate polarity alkaloids. These alkaloids might also contribute to the umami flavor of the plant’s leaves. However, identification the alkaloids and free amino acid composition of the crude protein is necessary to support these findings.